The Use of Dart Board Games as Strategy to Improve Students' Speaking Skill - Asiah, Nurdiati (SELL Journal : Scope of English Language Teaching, Linguistics, and Literature, 2020)
This study aims to improve students' speaking abilities. The method used in research is a quantitative method with True Experimental as a research design using the Pre-Test Post-test the researcher will only use one class chosen randomly from total of population. The study was conducted at Muhammadiyah 6 junior high School tieng. The sampling technique used was Cluster Random Sampling, in this study the authors used a class from class 7 for sampling, the data were analyzed statistically using t-test. The results of this study indicate; the average value of grade VII students is 68.57 Statistical calculations show that the results of t0 (t-observation)> tt (t-table). Where t-observation (t0) obtained is 10 while the value of t-table (tt) is 1,711 with a significant 5% (0.05) which is t0 greater than tt, thus alternative hypotheses (Ha) are accepted and null hypothesis (H0) rejected. Based on the results listed it can be concluded that the dart board method develops children's ability to improve students' speaking abilities.